Four new additions to Helvella (Helvellaceae, Pezizales) from Northern Thailand - Yu, Feng-Ming; Lei, Lei; Luangharn, Thatsanee; Zhao, Qi; Zhu, Ying-An (Frontiers in Microbiology, 2023)
Most species of Helvella have been described from temperate regions in Asia, Europe, and North America, but little is known about the genus from tropical regions. In this report, phylogenetic analyses of 11 newly collected saddle-like fungi from northern Thailand using three genetic markers [the nuclear large subunit ribosomal DNA (LSU), the heat shock protein 90 (HSP90), and the translation elongation factor 1-alpha (TEF),] confirm their assignment in Helvella. Two species were described as new, i.e., Helvella atroides and H. tomentosa, and two species, i.e., H. fistulosa and H. rugosa, were reported for the first time in Thailand. Details of macro- and microscopic characters and illustrations are provided for each species. To date, seven species of Helvella have been recorded in Thailand, and a key for identifying the Thai Helvella species is provided here.